PENGARUH HEALTH EDUCATION TENTANG PEMERIKSAAN PAYUDARA SENDIRI (SADARI) DALAM UPAYA DETEKSI DINI KANKER PAYUDARA PADA REMAJA PUTRI DI KELURAHAN POLEWALI : Effect Of Health Education About Check Breast Self (Sadari) In Early Detection Breast Cancer Youth Woman In Kelurahan Polewali - Ria Metasari, Andi (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2023)
Breast cancer does not only attack adults but has attacked teenagers. Health education is the first step in increasing the knowledge and abilities of adolescents, including health education about breast self-examination (SADARI) as an early detection to prevent breast cancer so that it can reduce the incidence of breast cancer for women. This study aims to determine the effect of health education on breast self-examination (SADARI) in early detection of breast cancer in adolescent girls in Sub-District of Polewali Tanete Riattang Barat, the Regency of Bone. This design uses a quasi-experimental with one group pretest post-test method. A total of 40 adolescents were sampled at the time of the study using a purposive sampling technique in accordance with the inclusion criteria. The results of the study based on the Wilcoxon Test, it was found that there was an increase in the level of knowledge before being given treatment with a mean value of 36.00 increasing to 88.00 after being given treatment with a p value = 0.000 while the ability to practice BSE before being given treatment with a mean value of 2.73 increased to 75.43 after being given treatment with p value = 0.000. This indicates that health education influences breast self-examination (SADARI) as a means of preventing breast cancer in adolescent girls earlier. For this reason, adolescents need to get more information about their reproductive health and receive regular and continuous counseling.